Ties that bind: The ambiguous role played by social capital in black working class first-generation South African students’ negotiation of university life - Vincent, L.; Hlatshwayo, M. (South African Journal of Higher Education, 2018)
In this article we examine the ambiguous role that social capital plays in first generation Black working class South African students’ negotiation of entry into an elite higher education institutional environment. First generation student experiences have a particular relevance in South Africa where student enrolment increased by 193 000 between 1993 and 2004, with many of the new entrants first-generation students. South African research on first-generation working class Black students has focused on the low proportion of these students who reach university at all and among those who do enter university, the significant number who perform poorly or drop out before completing their degrees. The role played by social capital (social networks, close friends, associations, clubs and other affiliations) in these students’ experiences of negotiating their entry into university has been little explored. Using a combination of in-depth interviews, observation and hierarchical mapping with 28 participants at one historically white South African university, we exam here how social networks play a significant role in providing much-needed support to first generation Black working class students as they negotiate entry into the alienating terrain of a historically white university. The paper argues however that when social capital networks are closed, tightly policed and inward looking, consisting only of individuals from similar backgrounds, such networks can serve to perpetuate disadvantage. In this context, the role of ‘brokers’ – trusted individuals who are able to act as bridges to wider, more information- and resource-rich networks – becomes critical.